The Connection between Extracurricular, Leisure Time Activities, Religiosity and the Reasons for Drop-out - Váradi, Judit; Demeter-Karászi, Zsuzsanna; Kovács, Klára (Central European Journal of Educational Research, 2019)
The interruption of tertiary education and the reduction in the dropout rate have been a central issue in educational sociology and education research. Exploring the possible reasons for dropping out can significantly contribute to reducing the trend. Our aim is to map the links between students dropping out and individual factors. Consequently, we investigate the connection between extracurricular and leisure-time activities, health behaviour and religiosity in relation to dropout. This is explained by the fact that one of the axioms of the literature on dropout is that belonging to civil networks usually strengthens the commitment to the successful completion of studies. In our analysis, we used the database created during the research carried out in 2018 by the Center for Higher Education Research and Development (CHERD-H) in the framework of project No. 123847 of the National Research, Development and Innovation Fund of Hungary, entitled The Role of Social and Organisational Factors in Student Dropout (DEPART 2018, N=605). Our results show that the neglect of study obligations among those who are disappointed in the course and further education is closely related to the shift in value preferences and an increase in the time spent with entertainment activities and partying. It can also be stated that students take part indifferent types of extracurricular activities only to a limited extent, and the different forms of participation in activities and religiosity are not related to the causes of dropout.